Soil microbial responses to nitrogen addition in arid ecosystems - Sinsabaugh, Robert L.; Belnap, Jayne; Rudgers, Jennifer; Kuske, Cheryl R.; Martinez, Noelle; Sandquist, Darren (Frontiers in Microbiology, 2015)
The N cycle of arid ecosystems is influenced by low soil organic matter, high soil pH and extremes in water potential and temperature that lead to open canopies and development of biological soil crusts (biocrusts). We investigated the effects of N amendment on soil microbial dynamics in a Larrea tridentata-Ambrosia dumosa shrubland site in southern Nevada USA. Sites were fertilized with a NO3-NH4 mix at 0, 7, and 15 kg ha-1 yr-1 from March 2012 to March 2013. In March 2013, biocrust (0-0.5 cm) and bulk soils (0-10 cm) were collected beneath Ambrosia canopies and in the interspaces between plants. Biomass responses were assessed as bacterial and fungal SSU rRNA gene copy number and chlorophyll a concentration. Metabolic responses were measured by five ecoenzyme activities (EEA) and rates of N transformation. By most measures, nutrient availability, microbial biomass and process rates were greater in soils beneath the shrub canopy compared to the interspace between plants, and greater in the surface biocrust horizon compared to the deeper 10 cm soil profile. Most measures responded positively to experimental N addition. Effect sizes were generally greater for bulk soil than biocrust. Results were incorporated into a meta-analysis of arid ecosystem responses to N.